(untitled) (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2024)
The characteristic properties of concrete depend on the quality of mortar. In order to improve the properties of hardened concrete, the mortar needs to have good performance. The property of mortar is affected by wet packing density, liquid film thickness, type and quality of binder, gradation of fine aggregates and binder to fine aggregates ratio. The commonly used alkali solutions to produce polymer mortar and concrete is cursed by carbon dioxide emissions. This study used alkali solution and water to investigate variation of packing densities and film thicknesses on paste and mortar mixes. of natural pozzolan and calcium hydroxide at ratio of 75P25CH and standard sand. The standard proctor compaction tools and procedures were adopted to attained the maximum values of packing density of 0.937 for mortar mixed with alkali solution, 0.919 for mortar mixed with water, 0.906 for paste mixed with alkali solution and 0.829 for paste mixed with water. For the case of film thicknesses, the optimum values obtained were 0.548 μm for mortar mixed with alkali solution, 0.248 μm for mortar mixed with water, 0.398 μm for paste mixed with alkali solution and 0.09 μm mixed with water. The results indicate that, alkali solution produced higher packing density and liquid film thickness than water for both paste and mortar and the packing density and liquid film thickness increases with the increase of number of compacting blows with 9 blows to 36 bows. The study recommends on the establishment of standard compaction effort and procedure.